The association between calcium intake, osteoporosis knowledge and osteoporosis health beliefs among post-menopausal women : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Nicholson, Colette (Massey University, 2024)
Background: Osteoporosis is the most prevalent metabolic bone disease globally. It is caused by excessive loss of bone mineral density (BMD), with a subsequent increase in fracture risk. The condition is costly in terms of healthcare and older adult quality of life. Older women are most likely to experience the onset of osteoporosis due to the cessation of oestrogen production during menopause. Though prevalence is thought to be underestimated, as much as 35.5% of females over 50 years of age are living with osteoporosis in most western countries. Compelling evidence exists that onset can be arrested among older females through ongoing diet and lifestyle choices to mitigate menopausal related loss of BMD. However, randomised control trials of various interventions designed to support positive bone health behaviours have delivered mixed long-term results. This indicates that engagement in positive bone health behaviours is complex. It is thought that actions may also be influenced by health beliefs rather than knowledge of osteoporosis. Health beliefs are also thought to change according to age, gender, and ethnicity. Previous New Zealand-based studies on osteoporosis bone health behaviours and beliefs have focussed on pre-menopausal women. Subsequently, the associations between osteoporosis knowledge, health beliefs, and bone health behaviours, among the vulnerable population of post-menopausal women are largely unknown. Objectives: To investigate the relationship between the bone health behaviour of calcium intake, osteoporosis knowledge, and health beliefs amongst post-menopausal New Zealand women. Methods: This study is a secondary data analysis of a cohort of 66 post-menopausal females from the “Footprint” study. Surveys completed by the participants included the osteoporosis knowledge test, the osteoporosis health belief survey, demographic questions, and a calcium food frequency questionnaire. Pearson’s and Spearman’s rho correlations were used to determine the relationship between calcium intake and the independent variables. Linear regression is used to identify predictors of calcium intake. Results: A weak negative correlation was found between the perception of severity (rs = -0.301, p = 0.017) and calcium intake, as well as a weak positive correlation with university level of education (rs = 0.355, p = 0.008). Following linear regression analysis, the benefits of exercise (β = 0.430, p = 0.007) was identified as the only health belief construct to predict calcium intake, accounting for 17.2% of the variation. Conclusions: The findings of this study suggest that there may be an association between calcium intake and health beliefs around osteoporosis in older women in New Zealand; however, further research with a larger sample size would be required to support these results.
Figure 2.1 (=Liang et al., 2021 Fig 1) was removed for copyright reasons.
Keywords: 321004 Nutritional science